Perspectivas sobre socialização de estudantes universitários com deficiência física: entre estigmas e vivências no meio acadêmico - Souza, Sara Barbarelli de (Universidade Federal de São Carlos, 2022)
This research investigated the perceptions and experiences that university students with physical disabilities (PWD) have about the relationship between socialization and stigma in the academic environment. As hypotheses, we have that: i) People without disabilities due to lack of preparation or moral and ethical values, do not know how to deal with the body of people with disabilities, in the sense that this marked body reveals barriers and differences ; ii) Misrepresentation that disability is a disease - negatively impacts social interactions and self-image of people with disabilities ; iii) hypothesis about the impacts of stigma on the experience and symbolic representation of people with disabilities. The general objective of the study was to investigate and understand, from the perspective of university students with physical disabilities, the relationship between stigma and experience in the academic environment. The specific objectives were: i) to investigate the representations about being a PCD; ii) investigate the history of entering and living in the university context and possible situations of stigmatization; iii) investigate social and affective-sexual relationships in the university context. The present study used procedures and techniques of the dialectical hermeneutic approach. It is an empirical, qualitative, descriptive-interpretative research, in which investigated the universe of experiences and representations about being a person with physical disabilities inserted in the academic environment. 5 university students (undergraduate and graduate) with physical disabilities and linked to public (4) and private (1) institutions participated in the research.The research instrument was a semi-structured interview script, in a virtual environment, depending on the health recommendations due to the pandemic by covid19. The interviews were carried out via the Google Meet virtual platform.The data obtained through the collection were treated from the thematic content analysis. In general, through content analysis, the objective is to transform inferences from a given context into specialized and scientific procedures (Bardin, 1979; Minayo, 2014). The research was based on the theoretical frameworks of Minayo (2014), where more specifically, with thematic content analysis, the objective is to discover the nuclei of meaning that are present in communication and that mean something to the intended analytical object. The analysis resulted in 07 thematic categories and their respective nuclei of analysis: 1. Disability stigmas - sought to highlight the meanings that the daily experiences of coping with stigma provided; 2. The affective/subjective dimension and the psychological effects of stigma; 3. Reconstruction of senses and meanings about being a PWD - perceptions of being and feeling as a person with a disability (initial perceptions about the body and about difference); 4. Construction of citizenship: Human and social rights - perception of oneself as a subject of rights; 5. Interaction and Intersubjectivity between people with disabilities and people without disabilities; 6. History of admission and permanence in higher education - previous and current educational trajectories that supported perceptions regarding obstacles and the desire to enter higher education; 7. The place of the body in the life of the PCD person. We emphasize that the social interaction between students with disabilities and students without disabilities was more inclusive and welcoming in higher education than in basic education; and the relevant social protagonism of PWD students was a factor in deconstructing stigmas in social and affective relationships in the academic environment.
Perspectives on socialization of university students with physical disabilities: between stigma and experiences in the university
Keywords: Deficiência física; Universitários; Socialização; Physical disability; College students; Socialization; CIENCIAS HUMANAS::PSICOLOGIA